The Awareness of Audiologists and Speech Language Pathologists among Doctors - Jamuna Dayalan1 , Suman Maji1 , Jerusha Biju1 , Subhashini Dhandayutham2 , Krishna Prasanth3, Bhumin (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: The purpose of this study is to survey the awareness of Audiologists and Speech Language Pathologistsamong Medical Professionals (Doctors, Postgraduate students and Undergraduate students) and to report thepreliminary survey results.Method: A survey was carried out by administering questionnaire consisting 20 questions. The questionsare designed to explore and investigate the field of Audiology and Speech Language Pathology (ASLP). Theparticipants were divided into two groups A and B, where group B is below 35 years and group A is 35 yearsand above.Result: The result of the study revealed that the overall awareness of ASLPs among Medical Professionalsvaried between fairly adequate knowledge to inadequate knowledge. Age does not have any influence onsignificant awareness on ASLPs.Conclusion: Hence the knowledge and awareness for audiologists and speech-language pathologists need toescalate among medical professionals. Future surveys should be conducted to reduce the lack of awareness of